Determinants of Poverty in East Java Metropolitan Area in 2010-2016 - Nur Sakinah; Hary Pudjianto (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2018)
This research aims to identify determinants of poverty and as well as to estimate poverty trend. We use secondary data that gathered from 7 regencies and cities in Gerbangkertosusila Area. Our data range from 2010 to 2016 and analysed with random effect model. Our result shows that per capita GRDP, level of health, employment opportunities and education variables have negative and significant impact on poverty variable in Gerbangkertosusila Area during 2010-2016 period. Whereas inflation rate variable has no effect on poverty. We also found that employment opportunities variable is the most influencing factor affecting the level of poverty. We recommend to increase employment opportunities by promoting investment in regency and city around the area, increasing attention to the education problems like reducing the number of children dropped out from school, optimizing education budgets, promote education scholarships as well as improving the quality of health services, and establishing synergies between regency and city.Keywords: Poverty, Metropolitan Area, Inflation.